Citizen Scientists’ Motivation to Participate in Environmental DNA (eDNA) Surveys: A Case Study on Monitoring Mammals in the UK - Holly A. Broadhurst; Elin E. Smith; Jake M. Jackman; Natalie Singleton; Darren Tansley; Robert Raynor; Naiara Guimarães Sales; Erinma Ochu; Allan D. McDevitt (Citizen Science: Theory and Practice, 2025)
Citizen scientists have become integral participants in biodiversity monitoring, and the demand for effective surveying efforts has sparked interest in utilizing environmental DNA (eDNA) for species monitoring, drawing volunteers into survey planning and sample collection. However, there remains a gap in understanding the motivations behind volunteer engagement in surveys that don’t involve direct observations of species, including the need to validate collected data and recognize volunteer contributions to ensure their satisfaction. To address this gap, we used questionnaires to assess volunteer science capital, motivation to participate, and their experiences during eDNA sampling. We trained ten conservation volunteers, all of whom were members of the Essex Wildlife Trust, to collect eDNA samples from two rivers and a beaver enclosure to detect terrestrial and semi-aquatic mammals. Citizen scientists were highly motivated and demonstrated high science capital, enabling them to develop innovative eDNA sampling methods and take enjoyment in contributing to meaningful scientific knowledge and helping their local wildlife. Additionally, citizen scientists detected more species compared with eDNA researchers, underscoring the value of local knowledge, and the longer sampling periods associated with typical citizen scientist projects. This case study highlights the benefits of involving citizen scientists in eDNA surveys, as sharing results led to meaningful discussions about the species detected and further enriched knowledge exchange. The case study’s limitations include small sample size and limited participant diversity in terms of age, gender, and ethnicity. However, the findings can inform future research with larger and more diverse participants.